ThuLEP technique for managing benign prostatic hyperplasia: Intraoperative and postoperative complications in a series of 42 consecutive cases: Complications in ThuLEP technique - Ergün, Müslüm; Sağır, Süleyman; Hacıbey, İbrahim (Journal of Surgery and Medicine, 2025)
Background/Aim: Data from the first series of 42 patients diagnosed with benign prostatic hyperplasia (BPH) who underwent Thulium laser prostate enucleation (ThuLEP) surgery at our clinic were retrospectively reviewed. The procedures were performed by a single physician with 10 years of endoscopic surgery experience. The purpose of this retrospective study was to add our results, which highlight potential complications during and after ThuLEP surgery, to the already reported ThuLEP results in the literature. Methods: Data from 42 patients with BPH who underwent ThuLEP surgery at Atlas University Hospital between January 2020 and January 2024 were retrospectively analyzed. Patients with a high international prostate symptom score (IPSS>7), a low quality of life score (QoL<3), a prostate volume ≥ 50 cc according to urinary ultrasonography, a peak urine flow rate (Qmax) ≤ 15 ml/s on uroflowmetry, a total serum prostate-specific antigen (tPSA) <4 ng/mL, and a negative biopsy tPSA ≥ 4 ng/mL were included in the study. All patients underwent pre-operative evaluations that included urinalysis, urine culture, tPSA, uroflowmetry, IPSS, QoL, urinary ultrasonography, prostate volume, postvoid residual urine volume (PVR), and sexual function (IIEF). ThuLEP surgery was performed en bloc using the “Omega Sign” technique in all patients. Results: Mean enucleation and morcellation times were 110±40 and 25±18 min, respectively. Mean resected prostate tissue weight was 40±25 g. Mean hospital stay and catheterization time were 40±12 and 36±10 h, respectively. Significant improvements were observed in post-operative IPSS, IIEF, QoL, Qmax, and PVR (P<0.05). Qmax increased, whereas PVR decreased. Post-operative hemoglobin values decreased initially (P<0.05) but returned to baseline at six months (P>0.05). Intra-operative complications included superficial bladder mucosal injury in two patients (4.76%), major capsular perforation in one patient (2.38%), and major perforation below the bladder neck between the five and seven o’clock positions in one patient (2.38%). Complications that developed in the first six months after surgery included urinary retention in one patient (2.38%), stress incontinence in two patients (4.76%), and urethral stricture in one patient (2.38%). Conclusion: Due to the steep learning curve for surgeons, ThuLEP surgery can initially cause complications, which are manageable. Despite these complications, current reports support its safety and effectiveness across a variety of prostate sizes. The ThuLEP technique offers patients several advantages, such as shorter hospital stays, shorter catheterization times, and fewer complications.